2010
DOI: 10.30638/eemj.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation Modeling and Measurements in Timisoara, Romania: Data and Model Quality

Abstract: This paper introduces the first station in Romania (Eastern Europe) outfitted for systematic monitoring of solar irradiance on tilted surfaces. The resulted database is in many aspects unique for Romania, allowing for the first time to derive specific parameters like diffuse fraction or sunshine number. Also for the first time, the data collected on tilted surfaces can be used to test models reported in literature and to recommend the most fitting for the region, as is detailed in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Hottel and Woertz, (2000) calculated the overall heat loss coefficient and the collector efficiency under different conditions such as the absence of cover, with single and double glazing under different ambient conditions, tilt angles, wind speeds, emissivity of both glass cover and absorber plate. Paulescu et al, (2010) discussed the influence of various parameters on the efficiency of solar collectors and concluded that at low solar insolation in the range of 200-600 w/m 2 double glazed collectors are superior to single glazed. Stanciu and Stanciu, (2014) examined the performance by changing the colors of solar collector.…”
Section: Bsjournalsmentioning
confidence: 99%
“…Hottel and Woertz, (2000) calculated the overall heat loss coefficient and the collector efficiency under different conditions such as the absence of cover, with single and double glazing under different ambient conditions, tilt angles, wind speeds, emissivity of both glass cover and absorber plate. Paulescu et al, (2010) discussed the influence of various parameters on the efficiency of solar collectors and concluded that at low solar insolation in the range of 200-600 w/m 2 double glazed collectors are superior to single glazed. Stanciu and Stanciu, (2014) examined the performance by changing the colors of solar collector.…”
Section: Bsjournalsmentioning
confidence: 99%
“…The following hypotheses are considered:  Solar radiation is determined by applying Hottel & Woertz model in clear sky conditions[1];  Measured data for ambient temperature are used [9];  Time dependent computations of the flat plate collector; time dependent global heat transfer coefficient and constant mass flow rate inside FPC; constant tilt all along the period, according to [10];  Constant mass of water inside the storage tank and uniform temperature distribution;  Constant global heat transfer coefficient for the storage tank;  Time dependent fluid properties, computed in EES environment [11]. Equation (1) is applied for the flat plate collector considering convection, conduction through insulation and radiation heat losses, and for the storage tank in transient operation so that inside water temperature variation in time is determined.…”
Section: Thermal Modelmentioning
confidence: 99%
“…In Romania, most of studies on solar energy generally referred to climate parameters (i.e. solar radation) necessary in assessing its potential [21,22,23,24], economic efficiency [25,26] or policy context [27] for its valorisation. Recently, some regional studies have focused on the environmental and socio-economic impacts of PV farms [28,29].…”
Section: Introductionmentioning
confidence: 99%